The impact of local labour on achieving quality standards in low cost housing - Maluleke, Thabitha Refilwe (My University, 2021)
The study seeks to establish the nature of the relationship between the use of local labour and the achievement of quality standards on the construction of low-cost housing. Poor quality of low-cost housing has been experienced gradually over the years, (Manomano and Tanga, 2018). Manomano and Tanga (2018), revealed that the low-cost houses that are being built have cracked walls, substandard doors and weak roofs and they pose a health risk to the intended habitants. In order to improve the quality in the construction of low cost houses this study conducted an investigation on how local labour impacts on the achievement of quality delivery of low cost houses. In the endeavours of establishing this relationship the study chose to conduct a case study on Ratanda housing project. The findings confirmed that the employment of local labour has an effect on the achievement of quality standards. The study also discovered that other factors that affect quality include inadequate material and lack of supervision. From the literature and the data gathered the study recommends that the contractor needs to improve quality communications in the project by keeping records of all activities that occur onsite and any correspondence concerning quality issues and improve the supervisory skills of the management team. And in local housing projects there has to be a system that allows an intensive training of labour before they work on the project to equip them with the necessary skills to work productively and effectively. The problem of adherence to quality management and compliance, if not addressed, will continue to cause unhappy beneficiaries, therefore creating an environment for service delivery protests. Potential injuries to inhabitants of the low-cost houses and potential liability to the state will arise
A research report submitted to the Faculty of Engineering and the Built Environment of the University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Science in Building, 2021